Reduce Flood Losses Of Kali Tanggul Using Spatial Based Technical Approaches - Prabowo Prabowo; Gusfan Halik; Entin Hidayah; Taqiudin Haq (U Karst, 2021)
Flood disasters frequently occurred in Jember Regency, East Java. It is usually caused by the overflow of the Tanggul River in the rainy season, especially in the downstream area. Flood control could be done by building dams, embankments, shortcuts, and other technical flood protections. Meanwhile, mitigation efforts such as developing thematic maps of flood inundation need to be done to minimize losses caused by the flood. This study aims to design a flood mitigation strategy technically. The flood control structure was proposed by designing a shortcut in Kali Tanggul. Its performance was analyzed to reduce flood inundation in the Tanggul watershed. The flood inundation modeling was carried out using spatial analysis using ArcGIS 10.1 and hydraulic analysis using HECRAS 5.0.3. Flood inundation results were compared with the Tanggul watershed flood map developed by UPT PUSDA Lumajang. Based on modeling results, flood control using shortcuts is considered an effective strategy for flood mitigation. It was indicated by the reduction of flood inundation distributions, flood inundation height, and flood-affected areas. The results show that the flood height decrease 0.47 up to 0.56 m